2021
DOI: 10.1111/jnc.15334
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous, synchronous zinc spikes oscillate with neural excitability and calcium spikes in primary hippocampal neuron culture

Abstract: Zinc has been suggested to act as an intracellular signaling molecule due to its regulatory effects on numerous protein targets including enzymes, transcription factors, ion channels, neurotrophic factors, and postsynaptic scaffolding proteins. However, intracellular zinc concentration is tightly maintained at steady levels under natural physiological conditions. Dynamic changes in intracellular zinc concentration have only been detected in certain types of cells that are exposed to pathologic stimuli or upon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 92 publications
(164 reference statements)
0
15
0
Order By: Relevance
“…Thus, buffering must allow zinc signals to occur, reach their targets, and then restore concentrations to steady-state levels. On the one hand, MT is a source of signaling Zn­(II) ions when it transduces redox signals into zinc signals or possibly as result of local pH changes due to an inherent pH dependence of the Zn­(II) affinity. , T, on the other hand, removes Zn­(II) ions from sites that are targets of the signaling Zn­(II) ions.…”
Section: Relating Metallothionein Thermodynamics and Kinetics To Cont...mentioning
confidence: 99%
“…Thus, buffering must allow zinc signals to occur, reach their targets, and then restore concentrations to steady-state levels. On the one hand, MT is a source of signaling Zn­(II) ions when it transduces redox signals into zinc signals or possibly as result of local pH changes due to an inherent pH dependence of the Zn­(II) affinity. , T, on the other hand, removes Zn­(II) ions from sites that are targets of the signaling Zn­(II) ions.…”
Section: Relating Metallothionein Thermodynamics and Kinetics To Cont...mentioning
confidence: 99%
“…Indeed, the concentration of glutamate in the synaptic cleft is estimated to reach the mM range after neuronal depolarization. Although the level of Zn increases to approximately 10 nM in the CSF under ischemic conditions, the Zn concentration in synapses is estimated to be 1–100 μM.‍ ( 28 ) Zhang et al ‍ ( 29 ) observed a spontaneous and synchronous “Zn spike” in cultured hippocampal neurons along with calcium (Ca) spikes. In such situations, the Zn concentration in synapses may become much higher.…”
Section: Roles Of Cu and Zn In The Synapsementioning
confidence: 99%
“…Elucidation of zinc's role in physiological or pathological conditions is particularly challenging because its multiple roles in cellular processes, [5,6,22]; its possible overlap with Ca, [23], and its mobility between "chelatable" and "non-chelatable" pools. ( [6].…”
Section: Metalsmentioning
confidence: 99%